Validation Results of Augmented Reality Media on Climate Change and Analysis of Students' Prior Knowledge on Global Warming Material in the “Kurikulum Merdeka” - Wulandari, Desi; Roudhoutul Aulia Rochim; Shofie Cahyani (Indonesia Approach Education, 2024)
This study aims to analyze the development process of augmented reality media on climate change and global warming created by the researcher, evaluate the assessment results by experts on the augmented reality climate change media, and analyze students' prior knowledge of climate change and global warming material. The research was conducted using a descriptive quantitative method with data analysis supported by SPSS software. The augmented reality media on climate change was developed through the Assemblr Studio web platform, covering topics such as global warming, the greenhouse effect, ENSO, La Niña, El Niño, and the neutral phase. The findings indicated that the media development procedure was analyzed using guidelines, both for developing the media and for its use. Furthermore, the analysis of students' prior knowledge in understanding climate change and global warming material showed satisfactory results. The impact of AR media on climate change and global warming materials includes the ability to enhance global awareness, increase scientific knowledge and environmental care attitudes, as well as foster proactive actions to reduce greenhouse gas emissions that cause global warming and lead to climate change. Future research is needed to analyze students' literacy understanding after the implementation of the augmented reality climate change media.